Denosumab and teriparatide transitions in postmenopausal osteoporosis (the DATA-Switch study): extension of a randomised controlled trial. Issue 9999 (19th September 2015) - Leder, Benjamin Z; Tsai, Joy N; Uihlein, Alexander V; Wallace, Paul M; Lee, Hang; Neer, Robert M; Burnett-Bowie, Sherri-Ann M
Summary: Background: Unlike most chronic diseases, osteoporosis treatments are generally limited to a single drug at a fixed dose and frequency. Nonetheless, no approved therapy is able to restore skeletal integrity in most osteoporotic patients and the long-term use of osteoporosis drugs is controversial. Thus, many patients are treated with the sequential use of two or more therapies. The DATA study showed that combined teriparatide and denosumab increased bone mineral density more than either drug alone. Discontinuing teriparatide and denosumab, however, results in rapidly declining bone mineral density. In this DATA-Switch study, we aimed to assess the changes in bone mineral density in postmenopausal osteoporotic women who transitioned between treatments. Methods: This randomised controlled trial (DATA-Switch) is a preplanned extension of the denosumab and teriparatide administration study (DATA), in which 94 postmenopausal osteoporotic women were randomly assigned to receive 24 months of teriparatide (20 mg daily), denosumab (60 mg every 6 months), or both drugs. In DATA-Switch, women originally assigned to teriparatide received denosumab (teriparatide to denosumab group), those originally assigned to denosumab received teriparatide (denosumab to teriparatide group), and those originally assigned to both received an additional 24 months of denosumab alone (combination to denosumab group). Bone mineral density at the spine, hip, and wrist were measured 6 months, 12 months, 18 months, and 24 months after the drug transitions as were biochemical markers of bone turnover. The primary endpoint was the percent change in posterior-anterior spine bone mineral density over 4 years. Between-group changes were assessed by one-way analysis of variance in our modified intention-to-treat population. This study is registered with ClinicalTrials.gov, number NCT00926380 . Findings: Between Sept 27, 2011, and Jan 28, 2013, eligible women from the DATA study were enrolled into DATA-Switch. Of 83 potential enrollees from the DATA study, 77 completed at least one post-baseline visit. After 48 months, the primary outcome of mean spine bone mineral density increased by 18·3% (95% CI 14·9–21·8) in 27 women in the teriparatide to denosumab group, 14·0% (10·9–17·2) in 27 women the denosumab to teriparatide group, and 16·0% (14·0–18·0) in 23 women in the combination to denosumab group, although this increase did not differ significantly between groups (for between-group comparisons, p=0·13 for the teriparatide to denosumab group vs the denosumab to teriparatide group, p=0·30 for the teriparatide to denosumab group vs the combination to denosumab group, and p=0·41 for the denosumab to teriparatide group vs the combination to denosumab group). For the bone mineral density secondary outcomes, total hip bone mineral density increased more in the teriparatide to denosumab group (6·6% [95% CI 5·3–7·9]) than in the denosumab to teriparatide group (2·8% [1·3–4·2], p=0·0002), but had the greatest increase in the combination to denosumab group (8·6% [7·1–10·0]; p=0·0446 vs the teriparatide to denosumab group, p<0·0001 vs the denosumab to teriparatide group). Similarly, femoral neck bone mineral density increased more in the teriparatide to denosumab group (8·3% [95% CI 6·1–10·5]) and the combination to denosumab group (9·1% [6·1–12·0]) than in the denosumab to teriparatide group (4·9% [2·2–7·5]; p=0·0447 for teriparatide to denosumab vs denosumab to teriparatide, p=0·0336 for combination to denosumab vs denosumab to teriparatide). Differences between the combination to denosumab group and the teriparatide to denosumab group did not differ significantly (p=0·67). After 48 months, radius bone mineral density was unchanged in the teriparatide to denosumab group (0·0% [95% CI −1·3 to 1·4]), whereas it decreased by −1·8% (−5·0 to 1·3) in the denosumab to teriparatide group, and increased by 2·8% (1·2–4·4) in the combination to denosumab group (p=0·0075 for the teriparatide to denosumab group vs the combination to denosumab group; p=0·0099 for the denosumab to teriparatide group vs the combination to denosumab group). One participant in the denosumab to teriparatide group had nephrolithiasis, classified as being possibly related to treatment. Interpretation: In postmenopausal osteoporotic women switching from teriparatide to denosumab, bone mineral density continued to increase, whereas switching from denosumab to teriparatide results in progressive or transient bone loss. These results should be considered when choosing the initial and subsequent management of postmenopausal osteoporotic patients. Funding: Amgen, Eli Lilly, and National Institutes of Health.